Kohinoor : the story of the world's most infamous diamond - Dalrymple, William
"The Koh-i-noor is the world's most famous diamond, but it has always had a fog of mystery around it. Now, using previously untranslated Sanskrit, Persian and Urdu sources, and the discoveries of modern gemmologists to reconstruct its original form, William Dalrymple and Anita Ananad blow away the legends to reveal its true history--stranger, and more violent, than any fiction."--From dust jacket.